Development Of A Prototype Of Industrial Respirators For Malay Male Users - Bahari, Muhammad Syahril (2010)

(untitled)
Majority of the respirator used in Malaysian industries are imported from America. Therefore the facial characteristics of Malaysian were not considered in the design process. Thus, leakages may occur when respirator does not fit users. This study aims to develop a prototype of a half-mask respirator using some new techniques. Facial anthrophometric data collection was conducted based on 47 samples of Malaysian Malay males. Statistical method was applied to establish design information from the data. Reverse engineering was utilized to make the mock-up part of the respirator from the face model using clay modeling. 3D scanner was used to digitize the mock-up part.